Pengembangan Sistem Backup Server EPrint dengan Ubuntu 24.04 ke Cloud Storage Nextcloud (Studi Kasus: Sekolah Tinggi Pariwisata (STP) Sahid Surakarta): Studi Kasus: Sekolah Tinggi Pariwisata (STP) Sahid Surakarta - Paryanta Paryanta; Ernes Cahyo N.; Muhammad Johan Fatoni (Elkom: Jurnal Elektronika dan Komputer, 2026)
Managing scientific archive data on the EPrints Server at STP Sahid Surakarta faces issues with manual backups using WinSCP. This procedure leads to potential human error and the risk of data loss due to local storage, thus threatening important institutional information. The purpose of this research is to develop a scheduled automatic backup system for an Ubuntu 24.04-based Eprints server, utilizing two Virtual Private Servers (VPS) and Nextcloud as cloud storage. The development method used is the Software Development Life Cycle (SDLC) Waterfall model, which includes analysis, design, implementation, and testing. The system implementation involves using bash scripts, cron, mysqldump, tar, and rclone for backup and restore functions. The system's functionality is verified through Black Box Testing. The test results show that the automatic backup system works consistently and as planned. Additionally, the restore function successfully recovered the entire data component and rolled back old data, complete with satisfactory activity log recording. This system provides a more efficient and controlled backup solution, addressing the weaknesses of the old system analyzed using the PIECES framework (performance, information, economy, control, efficiency, and service).